Assessing the BIM Software Application in Quantity Surveying Practice - Nurul Aini, Osman; Suhaida, S.K.; Nadeera, Abdul Razak (INTI International University, 2019)
Building Information Modeling (BIM) is a technology and a new buzzword which being used and is gaining a momentum within the construction industry in Malaysia. For the past few years the wave of BIM had been hitting the shores of construction industry in Malaysia. It has the potential to revolutionize the quantity surveying practice. However, it appears that quantity surveyors (QS) are still lagging behind in BIM application compared to other professionals. It is still generally underexplored the application and usage of BIM software in their practice. This research attempts to examine the usage of BIM software in quantity surveying practice. The scope of this research limited in pre-construction phase. The list of BIM software that related to enhance the quantity surveying performance are found through literatures and verify through pilot study. The findings indicate that through 9 different types of BIM software, Autodesk Quantity Takeoff is the most popular among quantity surveying practice. These findings provide an evidence that QS had been integrated their practice into BIM technology.